2010
DOI: 10.1007/s10620-010-1417-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Impact of Hepatic Steatosis on the Response to Antiviral Therapy in Saudi Patients with Genotypes 1 and 4 Chronic Hepatitis C

Abstract: Our study confirms the high prevalence of steatosis in HCV-G4 and HCV-G1 patients, but with no difference in the grade or score of steatosis between the two genotypes. The grade of steatosis correlates with GGT, platelet count, and BMI, while the NAS score of steatosis correlates with response to antiviral therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…However, this rate of disease progression changes over time in women as postmenopausal women have increased rates of fibrosis compared with women of reproductive age because they have lost the protective effects of estrogen. Another study, which is consistent with our results, showed that steatosis associated with chronic hepatitis C was disproportionally more frequent in females 34 .…”
Section: Discussionsupporting
confidence: 93%
“…However, this rate of disease progression changes over time in women as postmenopausal women have increased rates of fibrosis compared with women of reproductive age because they have lost the protective effects of estrogen. Another study, which is consistent with our results, showed that steatosis associated with chronic hepatitis C was disproportionally more frequent in females 34 .…”
Section: Discussionsupporting
confidence: 93%
“…In some studies, low baseline GGT level was shown to be an independent predictor of a SVR 9-11,13,15,17. However, these studies did not fully evaluate other confounding factors, such as the presence of hepatosteatosis,19,21,22 bile duct injury,19,23 the degree of liver fibrosis,11,20 alcohol abuse,18,24 and gender,17 which might affect both GGT levels and SVR rates.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that some of the findings of Ziada et al have been reported by previous studies in other genotypes and in HCV-4-infected patients as well. The prevalence of steatosis in HCV-4-infected patients has been documented in a few previous studies reporting a prevalence of approximately 40% (3)(4)(5). In the study by AlQaraawi et al (3), for example, 43% of patients showed mild, 42% moderate and 15% severe steatosis (3).…”
mentioning
confidence: 91%
“…The prevalence of steatosis in HCV-4-infected patients has been documented in a few previous studies reporting a prevalence of approximately 40% (3)(4)(5). In the study by AlQaraawi et al (3), for example, 43% of patients showed mild, 42% moderate and 15% severe steatosis (3). These numbers are generally similar to what has been reported in HCV genotype 1 patients.…”
mentioning
confidence: 91%
See 1 more Smart Citation